2020
DOI: 10.1002/1873-3468.13937
|View full text |Cite
|
Sign up to set email alerts
|

Low oxygen tension differentially regulates the expression of placental solute carriers and ABC transporters

Abstract: Low oxygen concentration, or hypoxia, is an important physiological regulator of placental function including chemical disposition. Here, we compared the ability of low oxygen tension to alter the expression of solute carriers (SLC) and ABC transporters in two human placental models, namely BeWo cells and term placental explants. We found that exposure to low oxygen concentration differentially regulates transporter expression in BeWo cells, including downregulation of ENT1, OATP4A1, OCTN2, BCRP, and MRP2/3/5,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 101 publications
1
9
0
Order By: Relevance
“…Changes in oxygen tension within the placental circulation also occur throughout pregnancy, and this can be affected by maternal conditions such as preeclampsia. Studies in cultured placental explants and BeWo cells have shown that hypoxia alters expression of a number of transporters including BCRP, P-gp, OATP2B1, and several MRPs [ 180 , 187 ]. Hypoxic conditions were also found to impact expression of regulatory nuclear factors involved in transporter regulation, including the Aryl hydrocarbon receptor (AHR), Nuclear factor erythroid 2-related factor 2 (NRF2), and Retinoid X receptor alpha (RXR-α) [ 187 ].…”
Section: Transporter Regulationmentioning
confidence: 99%
See 2 more Smart Citations
“…Changes in oxygen tension within the placental circulation also occur throughout pregnancy, and this can be affected by maternal conditions such as preeclampsia. Studies in cultured placental explants and BeWo cells have shown that hypoxia alters expression of a number of transporters including BCRP, P-gp, OATP2B1, and several MRPs [ 180 , 187 ]. Hypoxic conditions were also found to impact expression of regulatory nuclear factors involved in transporter regulation, including the Aryl hydrocarbon receptor (AHR), Nuclear factor erythroid 2-related factor 2 (NRF2), and Retinoid X receptor alpha (RXR-α) [ 187 ].…”
Section: Transporter Regulationmentioning
confidence: 99%
“…Studies in cultured placental explants and BeWo cells have shown that hypoxia alters expression of a number of transporters including BCRP, P-gp, OATP2B1, and several MRPs [ 180 , 187 ]. Hypoxic conditions were also found to impact expression of regulatory nuclear factors involved in transporter regulation, including the Aryl hydrocarbon receptor (AHR), Nuclear factor erythroid 2-related factor 2 (NRF2), and Retinoid X receptor alpha (RXR-α) [ 187 ]. Endogenous signaling proteins affecting growth or angiogenesis, such as the epidermal growth factor, insulin growth factor, and the soluble fms-like tyrosine kinase-1 (sFlt-1), have been shown to regulate BCRP [ 28 , 174 , 181 , 188 ].…”
Section: Transporter Regulationmentioning
confidence: 99%
See 1 more Smart Citation
“…Transporter systems are adapted to the environment through diverse regulatory mechanisms—often linking multiple transporters into coordinately regulated networks. Examples of these networks are revealed in placental development where environmental signals such as hypoxia can alter levels of multiple transporters simultaneously [29].…”
Section: Abc Transporters and The Environmentmentioning
confidence: 99%
“…Contrastingly, the local hypoxic environment can boost the development, invasion, and tumor cell metastasis, and a chronic hypoxic environment confers resistance to chemotherapy. Accordingly, alleviating local hypoxia is instrumental in improving the antitumor effect. In addition, oxygen concentration can also affect the repair of bone defects after osteosarcoma excision .…”
Section: Introductionmentioning
confidence: 99%